APPLICATION OF A CONTEXTUAL APPROACH IN HISTORY LEARNING TO ENCOURAGE STUDENTS' CRITICAL THINKING AT SMAN 3 MEDAN - Daniel Riadi Sianipar; Abd Haris Nasution; Masniar Sihotang (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
The contextual approach has become the main focus in efforts to improve learning at various levels of education. This study aims to investigate the application of a contextual approach in history learning to improve students' critical thinking skills at SMA Negeri 3 Medan. The research method used was classroom action research with class XI science student participants. The research was conducted in three cycles, with each cycle consisting of planning, implementation, observation and reflection. Data was collected through observation, interviews and document analysis. The research results show that the application of a contextual approach is effective in improving students' critical thinking skills. Students demonstrate improvements in their ability to analyze historical context, identify patterns, and relate learned information to contemporary situations. The implications of this research provide direction for the development of more effective curriculum and learning strategies to facilitate students' critical thinking in the context of history learning at the high school level. The implications of this research highlight the importance of developing innovative and relevant learning strategies for improving the quality of education, as well as the importance of support and cooperation from various related parties. Recommendations for future research include exploring the long-term impact of contextual approaches, factors influencing their successful implementation, and collaboration between educational stakeholders. Thus, this research provides a valuable contribution to the understanding of effective learning strategies for improving students' critical thinking skills in the field of history, as well as providing a basis for the development of better education in the future.